Sanksi Pelatihan Kerja di Bawah Minimum (Studi Putusan Nomor 45/Pid.Sus-Anak/2025/PN Sby) - Damayanti, Afina; Rusdiana, Emmilia (Diktum: Jurnal Ilmu Hukum, 2026)
The aim is analyzes the suitability of imposing work training for children aligns with the regulation contained in Law Number 11 of 2012 “Law on the Juvenile Criminal Justice System”. This study uses a normative method with state approach, case approach. Result is judges consider the children’s psychological condition, background, and to ensure the child can continue their education, and impose work training sanctions that are below the minimum criminal penalty. These considerations reflect the existence of judicial discretion authority in deciding the appropriate sanctions for children. The judge is guided by Sema number 1 of 2017 point 5 letter a which basically stipulates that the minimum criminal threat in Article 79 paragraph (3) doesn’t apply if the perpetrator is a child, besides that the judge also weighs the main principle which is “The best interest for the child”. Discretion in sentencing children needs to be accompanied by strong and clear legal arguments or considerations to ensure legal certainty without neglecting the goal of restorative justice.